Implementasi Switch Openflow Berbasis Software Dengan Memanfaatkan Raspberry Pi Untuk Infrastruktur SDN - Imam Santoso; Mochammad Hannats Hanafi Ichsan; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Software-Defined Networking (SDN) is a dynamic, manageable, adaptable and cost-efficient architecture. The Raspberry software-based openflow switch is currently untested, so it still can not be the right reference to replace dedicated openflow switch devices. This study aims to implement OpenvSwitch to be applied to Raspberries so as to make it an openflow switch that can be used within the SDN network and then test the performance of Raspi switches, throughput, packet loss and delay. The results obtained from this research that Raspberry openflow switches can be used to replace dedicated openflow switches on a small scale such as office scope but not for large scale companies like companies due to bandwidth limitation on USB to Ethernet adapters, as well as RAM from Raspberry. Based on the results of throughput testing, throughput will decrease as the number of clients increases. While based on packet loss test results, packet loss will increase significantly when the number of clients more than 3. Then based on delay testing, the first test has a longer delay compared to the next test, this is because in the first ICMP (ping) packet, the ARP process occurs while in the second and so on does not do the ARP process because the information about ARP already exists in the ARP cache.